Cosmetic Keratopigmentation in Sighted Eyes: Medium- and Long-term Clinical Evaluation. Issue 3 (28th March 2021) - D'Oria, Francesco; Alio, Jorge L.; Rodriguez, Alejandra E.; Amesty, Maria A.; Abu-Mustafa, Sabat K.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: To assess the medium- and long-term outcomes of keratopigmentation (KTP) as a surgical alternative to change the cosmetic appearance of healthy eyes. Methods: A prospective, interventional, consecutive, multicenter, series of cases of cosmetic KTP was included in the study. Forty consecutive patients underwent KTPs with mineral micronized pigments using a femtosecond laser–assisted intrastromal or superficial technique. Main outcomes were cosmetic evaluation, subjective patients' satisfaction, and complications. The outcomes were evaluated at 6 months after the last operation and then yearly. Results: This study included 79 eyes of 40 patients, with a mean age of 34 ± 11 years; femtosecond laser–assisted intrastromal keratopigmentation was performed in 39 patients (97.5%) and superficial automated keratopigmentation in 1 patient. Mean follow-up was 29 months (range 6–69). Observer's evaluation was excellent in 90% of cases, and patient's satisfaction was excellent in 92.5% of cases. Twenty-eight eyes (35.4%) were reoperated; of them, 7 eyes (8.9%) had 2 color touch ups and 4 eyes (5.1%) had 3 color touch ups. After the retreatments, all the patients were satisfied with the cosmetic aspect. Light sensitivity at first month was the most common complication (30%), followed by change in the color (7.5%), color fading (5%), and visual field limitations in a case with 4.5-mm pupil size (2.5%). One patient with a previous laser in situ keratomileusis developed corneal ectasia. Conclusions: Cosmetic KTP achieves good cosmetic results and is associated with high patient satisfaction. Most of the complications could be managed adequately. It might offer a safe and effective new surgical alternative for those patients motivated to change the apparent color of their eyes.